Implementation of communication and interaction management in distributed environmental projects - Khrutba, Andrii; Morozov, Victor; Khrutba, Yuliia; Tkachenko, Valentyna; Lysak, Roksolana (Technology audit and production reserves, 2021)
The object of research is the management of communication processes that occur between different stakeholders in project activities in the implementation of distributed environmental projects. The research is based on the application of the basic provisions of communication management in project management methodologies, including Green Project Management used to study the features and factors influencing individual processes in distributed environmental projects. The paper also applies the current provisions, methodological approaches to set theory and systems analysis (to formalize management processes, development of system models); classical and applied project management standards; expert evaluation methods for quantitative evaluation of criteria; methods of mathematical modeling, etc. The information base of the research is statistical data on the implementation of projects, the results of own research. The main hypothesis of the study is the assumption that a significant impact on the outcome of the implementation of distributed environmental projects is determined by the successful management of communications between stakeholders in the development and implementation of the project. Because the formation of an effective communication management mechanism in distributed environmental projects ensures the receipt of the project product with minimal risks. The interrelation of management of communications and interactions in the distributed projects and features of application of the concept of Green Project Management for management of nature protection projects is shown. Peculiarities of interaction management in distributed environmental projects are analyzed. The method of interaction management in nature distribution distributed projects is offered. The method of creation of a communication platform for realization of the coordinated management of communications in the distributed projects is offered. With the help of the method it is possible to coordinate the planned actions of the project participants on a set of compromise and related solutions to implement the tasks that are the best results of the project in accordance with the functions for benefits. It is shown to increase the efficiency of the interaction management process in distributed environmental projects to ensure effective communication in the interaction of stakeholders in distributed environmental projects under the condition of unclear information about the real state of the level of achievement of stakeholder expectations.